The Influence of Financial Soundness on Financial Performance in the Banking Sector Listed on the IDX (International Journal of Scientific Research and Management (IJSRM), 2022)
Financial performance is an analysis used in assessing a company whether the company has used its funds properly and correctly. Because banking has a big role in economic activity, banks need to maintain their financial performance in helping to improve the economy of a country. The purpose of this study is to see the effect of financial soundness on financial performance. The implication of the research that has been done is to provide direction for financial managers in maintaining financial health which can affect financial performance. This study uses CAMEL variables, namely capital adequacy, asset quality, efficiency management, income quality, and liquidity. While the dependent variable uses ROE and NIM. This research was conducted using data from 27 banking sector companies listed on the IDX within a period of 5 years (2017-2021) and also used a panel data regression model in its testing. The results of the research conducted show that capital adequacy, asset quality, income quality, and liquidity have a significant positive effect on financial performance. Efficiency management has a significant negative effect on financial performance. The implication of the research that has been done is to provide direction for financial managers to improve their management efficiency because it still has a negative influence on financial performance. For investors, investors should choose high financial performance